Acceptance of Artificial Intelligence (ChatGPT) Among Trainee Teachers in Higher Education - María Napal Fraile; Leire Badiola (Trends in Higher Education)
The deployment of artificial intelligence has also reached the classroom, especially in higher education. Despite the reluctance among teachers, and the risks and threats present, the tool also has many potential advantages. This study analyzes the knowledge, acceptance, and perception of the use of ChatGPT among Secondary Teaching Master’s degree students in two universities of Northen Spain, by means of a questionnaire based on the UTAUT2 model, translated into Spanish and Basque, and answered by 60 trainee teachers. The results show a good knowledge and perception of user-friendliness, but low motivation, intention to use, and effective use. The benefits perceived by prospective teachers include speed in obtaining information, assistance with repetitive tasks, and positive impacts on motivation; while the risks identified include plagiarism and an over-reliance on technology. The benefits for teachers included assistance with receiving ideas for class and preparation or translation of teaching materials and evaluation tools, while attributing less importance to marking or automating feedback. Given its widespread presence, it is concluded that there is a need to improve teacher training in the use of AI to foster more effective integration and a more positive perception of these technologies in education.